Inflammatory Molecules in Aqueous Humour and on Ocular Surface and Glaucoma Surgery Outcome - Barbara Cvenkel; Andreja Nataša Kopitar; Alojz Ihan (Hindawi Limited, 2010)
Purpose. To investigate the influence of inflammatory molecules in the aqueous humour and on the ocular surface on the outcome of glaucoma surgery. Methods. Thirty patients who needed antiglaucomatous surgery were included. The interleukin- (IL-) 8, IL-1𝛽, IL-6, IL-10, tumour necrosis factor- (TNF-) 𝛼; and IL-12 were determined from aqueous humour preoperatively and the imprints of conjunctiva were analysed for expression of human leukocyte antigen- (HLA-)-DR after surgery by flow cytometry. The success of trabeculectomy was defined as intraocular pressure less than 21 mmHg without antiglaucoma medication. Results. Eyes with trabeculectomy failure at 3 months showed significantly higher TNF-𝛼 and IL-6 levels in the aqueous than eyes with successful surgery. Increased expression of HLA-DR on epithelial cells and antigen-presenting cells was not associated with the trabeculectomy outcome. Conclusions. Higher preoperative levels of TNF-𝛼 and IL-6 in aqueous humour may contribute to the development of inflammatory milieu and were associated with worse outcome of glaucoma surgery.